The direct medical costs of breast cancer in Iran: analyzing the patient′s level data from a cancer specific hospital in Isfahan - Majid Davari (International Journal of Preventive Medicine, 2013)
Background: Breast cancer is one of the main causes of mortality and morbidity world-wide. The estimation of the direct medical costs of breast cancer can help payers of the cost to understand the burden of breast cancer on their limited financial resources as well as the society. Methods: We used a cross-sectional study to calculate the direct medical costs of breast cancer among women in Isfahan, Iran. The medical records of all patients which were registered in Seyed Al-Shohada Hospital between March 2005 and March 2010 were reviewed. The relevant data from patients′ profiles extracted. The direct medical costs of received services were calculated with both public and private tariffs. Results: The total numbers of 467 patients in various disease stages were included into the study. The average age of patients was 49 years. The average direct cost per patient per month in stages I to IV were 222.17, 224.61, 316.51 and 828.52 US$, respectively. The surgery cost was the main cost driver for stages I and II with private tariffs. However for stages III and IV, the medication cost was the main cost component for managing breast cancer . Conclusions: The direct economic cost of breast cancer in Iran is very high; nonetheless, as the age of breast cancer in Iran is nearly 10 years lower than Western countries, the burden of the disease in Iran is expected to be significantly high. Medication therapy is the main cost component of the breast cancer.